IDENTIFIKASI KARAKTERISTIK BIOFISIK DAS CILIWUNG TENGAH - Rini - Fitri; Nur Intan Simangunsong; Nuraida Nuraida (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2022)
Abstract: Watersheds (DAS) in Indonesia are experiencing degradation due to population growth that changes land functions for economic. The purpose of this research is to identify the biophysical characteristics of the watershed as the basis for planning the management of the Central Ciliwung watershed. The method used is a field survey; this research was carried out in three stages, namely (a) primary and secondary data collection, (b) identification and analysis of biophysical characteristics in the Central Ciliwung watershed including soil physical conditions, slope and land use, (c) results of analysis of biophysical characteristics of the Central Ciliwung watershed. It is displayed spatially. The results show that the area of the Central Ciliwung watershed is 15,706.73 Ha, dominated by flat topography of 9576.86 Ha or 60.97% of the total watershed area. Land use for settlements is the most extensive, namely 12891.53 ha with a percentage of 82.06% of the total area of the watershed. Soil type in general is latosol association covering an area of 13151.36 Ha with a percentage of 83.74% of the total watershed area.Abstrak: Daerah Aliran Sungai (DAS) di Indonesia mengalami degradasi akibat dari pertambahan penduduk yang merubah fungsi lahan untuk kepentingan ekonomi. Tujuan dari penelitian ini adalah mengidentifikasi karakteristik biofisik DAS sebagai dasar perencanaan pengelolaan DAS Ciliwung Tengah. Metode yang digunakan adalah survei lapang; penelitian ini dilaksanakan melalui tiga tahap yaitu (a) pengumpulan data primer dan data sekunder, (b) identifikasi dan analisis karakteristik biofisik di DAS Ciliwung Tengah meliputi keadaan fisik tanah, kemiringan lereng dan penggunaan lahan, (c) hasil analisis karakteristik biofisik DAS Ciliwung Tengah ini ditampilkan secara spasial. Hasil penelitian menunjukkan bahwa luas DAS Ciliwung Tengah sebesar 15,706,73 Ha, didominasi oleh jenis topografi datar seluas 9576,86 Ha atau 60,97 % dari total luas DAS. Penggunaan lahan untuk Pemukiman merupakan paling luas yaitu 12891.53 Ha dengan persentase 82,06 % dari total luas keseluruhan DAS. Jenis tanah pada umumnya adalah asosiasi latosol seluas 13151.36 Ha dengan persentase 83.74 % dari total luas DAS.